2009
DOI: 10.1074/jbc.m807866200
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Blood Group ABH Type 1 Determinants by the FedF Adhesin of F18-fimbriated Escherichia coli

Abstract: F18-fimbriated Escherichia coli are associated with porcine postweaning diarrhea and edema disease. Adhesion of F18-fimbriated bacteria to the small intestine of susceptible pigs is mediated by the minor fimbrial subunit FedF. However, the target cell receptor for FedF has remained unidentified. Here we report that F18-fimbriated E. coli selectively interact with glycosphingolipids having blood group ABH determinants on type 1 core, and blood group A type 4 heptaglycosylceramide. The minimal binding epitope wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 66 publications
4
64
0
Order By: Relevance
“…However, Coddens et al (2009) observed that the E. coli F18 receptor is a type 1 H antigen catalyzed by a2-fucosyltransferase that is encoded by FUT2 as opposed to a type 2 H antigen catalyzed by a1-fucosyltransferase that is encoded by FUT1, and Moonens et al (2012) and Lonardi et al (2013) validated these results. Additionally, FUT1 glycosyltransferase converts type 1 H precursors into type 1 H blood group antigens (Kyprianou et al, 1990;Liu et al, 1998;Mathieu et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…However, Coddens et al (2009) observed that the E. coli F18 receptor is a type 1 H antigen catalyzed by a2-fucosyltransferase that is encoded by FUT2 as opposed to a type 2 H antigen catalyzed by a1-fucosyltransferase that is encoded by FUT1, and Moonens et al (2012) and Lonardi et al (2013) validated these results. Additionally, FUT1 glycosyltransferase converts type 1 H precursors into type 1 H blood group antigens (Kyprianou et al, 1990;Liu et al, 1998;Mathieu et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
“…In this study, the piglet specimens had been weaned for 1 week, and weaned piglets are very susceptible to E. coli F18 infections at this age (35 days old). The E. coli F18 receptor is a type 1 H antigen of the ABO blood group and a glycosphingolipid derivative (Coddens et al, 2009). Studies reported that ABH blood group antigens were primarily synthesized by the globo-and lactose-series of glycosphingolipid biosynthetic pathways (Hakomori, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This test was performed as described by Coddens et al (27); more details are in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…This work examined the specificity of the FedF adhesin tip through structural and site-directed mutagenesis studies. A region for binding to ABH blood group glycans associated with pig enterocytes was defined [5]. Significantly, another region of FedF was identified that interacts with glycosphingolipids and was proposed to be required for initial interactions with lipid bilayers.…”
Section: Abstract: Apec • Ehec • Epec • Escherichia Coli • Etec • Mucmentioning
confidence: 99%